Rosmarinic Acid, a New Polyphenol from Baccaurea ramiflora Lour. Leaf: A Probable Compound for Its Anti-Inflammatory Activity - Talambedu Usha; Sushil Kumar Middha; Malay Bhattacharya; Prakash Lokesh; Arvind Kumar Goyal (MDPI AG, 2014)
Despite several pharmacological applications of Baccaurea ramiflora Lour., studies on the influence of its polyphenol content on pharmacological activity such as anti-inflammatory properties have been scarce. Here we evaluated in vitro antioxidant activity, poyphenolics by HPLC and the anti-inflammatory potential of the methanolic leaf extract of Baccaurea ramiflora (BME) and its protective effects in carrageenan-induced paw edema model of inflammation in rats. The BME extract contained 79.06 ± 0.03 mg gallic acid equivalent (GAE)/g total polyphenols, 28.80 ± 0.01 mg quercetin equivalent (QE)/g flavonoid and 29.42 ± 0.01 μg cathechin equivalent/g proanthocyanidin respectively and rosmarinic acid (8 mg/kg) as a main component was identified by HPLC. Results demonstrate that administration of BME at the dose of 200 mg/kg can reduce paw edema by over 63%, and it exhibits a dose-response effect. Depending on concentration, the extract exerted scavenging activity on DPPH radical (IC50 36.4 μg/mL), significantly inhibited IL-1β (4.4 pg/mg protein) and TNF-α (0.21 ng/μg protein). Therefore, we conclude BME causes a substantial reduction of inflammation in in vivo models. We propose that rosmarinic acid and similar phenolic compounds may be useful in the therapy of inflammation-related injuries.